HARMONY BETWEEN SCIENCE AND SPIRITUALITY: A STUDY OF AL-GHAZALI’S PHILOSOPHY OF EDUCATION - Winda Sri Handayani; Ninda Alfia; Maryadi (STKIP Subang, 2024)
The great Islamic philosopher Al-Ghazali believed that knowledge is not only about facts, but also about moral and spiritual values. This article discusses how Al-Ghazali saw the relationship between science and spirituality in education. The purpose of this article is to analyze and understand how Al-Ghazali combines science and spirituality in teaching. The writing of this article uses qualitative analysis of several articles and experts' views on Al-Ghazali and Education. The analysis shows that Al-Ghazali emphasized the importance of balance between scientific knowledge and moral values in Education. He classified knowledge into various categories, including religious and rational sciences, and emphasized the role of the teacher as a crucial moral guide in shaping students' characters. The findings suggest that the application of Al-Ghazali's principles in modern education can help create a well-rounded individual, who is not only intellectually intelligent but also has high moral and spiritual awareness.